2018
DOI: 10.1210/js.2018-00086
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cushing Syndrome Due to an ACTH-Producing Pheochromocytoma: A Case Presentation and Review of the Literature

Abstract: Adrenocorticotropic hormone (ACTH)-dependent Cushing syndrome is rarely caused by a pheochromocytoma. We present a case of a 46-year-old woman who developed severe hypertension, hypokalemia, and typical Cushingoid features. Investigations revealed extremely high metanephrine, cortisol, and ACTH levels. Imaging showed a 3.8-cm left adrenal mass. Preoperative control of hypertension and hypokalemia was very challenging. The patient was cured after surgical removal of the adrenal mass. We followed this by a revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 51 publications
1
57
0
3
Order By: Relevance
“…Our patient did not have any evidence of Cushing's syndrome when he was first diagnosed with a phaeochromocytoma, but developed severe Cushing's syndrome within weeks. A recent literature review by Gabi et al confirmed that rapid onset of hypercortisolism appears to be a feature of ACTH-secreting phaeochromocytomas, unlike the insidious onset of other forms of ACTH-dependent Cushing's syndrome (1). Like our patient, the majority of patients had severe Cushingoid symptoms due to the circulating high levels of ACTH and cortisol.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our patient did not have any evidence of Cushing's syndrome when he was first diagnosed with a phaeochromocytoma, but developed severe Cushing's syndrome within weeks. A recent literature review by Gabi et al confirmed that rapid onset of hypercortisolism appears to be a feature of ACTH-secreting phaeochromocytomas, unlike the insidious onset of other forms of ACTH-dependent Cushing's syndrome (1). Like our patient, the majority of patients had severe Cushingoid symptoms due to the circulating high levels of ACTH and cortisol.…”
Section: Discussionsupporting
confidence: 71%
“…Like our patient, the majority of patients had severe Cushingoid symptoms due to the circulating high levels of ACTH and cortisol. Severe hypokalaemia is a feature reported in 95% of those cases (1). High circulating levels of cortisol exhibit mineralocorticoid activity after saturation of the 11ß-hydroxysteroid dehydrogenase type 2, the enzyme responsible for its metabolism, thus causing hypokalaemia (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pheochromocytoma/paraganglioma: These catecholamine-secreting endocrine tumors are a rare cause of EAS, and are responsible for less than 5% of all reported EAS cases (56,57,58,59). They are mostly unilateral, localized and retroperitoneal (18,51,52,53,54).…”
Section: (C) Abdominal and Retroperitoneal Netsmentioning
confidence: 99%
“…PPGLs are more frequent in certain groups, for example, in patients with adrenal incidentalomas with 0.6% to 4.2% being affected but is otherwise generally rare . Most PPGLs are nowadays diagnosed due to an incidentaloma, then due to catecholamine excess symptoms and finally because of screening in a previously known familial syndrome (eg, multiple endocrine neoplasia type 2, von Hippel Lindau syndrome, neurofibromatosis type 1, and mutations in succinate dehydrogenase B, C, and D) Cushing's syndrome due to ectopic ACTH‐production from a PPGL can occasionally occur, and thus all adrenal tumors should have a 1 mg overnight dexamethasone suppression test to exclude cortisol excess . Sometimes an adrenal medullary hyperplasia may be the culprit of catecholamine excess …”
Section: Introductionmentioning
confidence: 99%